THE EFFECT OF SQUAD JUMP TRAINING ON THE ACCURACY OF SMASH IN EXTRACURRICULAR VOLLEYBALL GAMES AT SMPN 17 KOTA BANDA ACEH - Munzir; Septi Hariansyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to examine the effect of squad jump training on smash accuracy in volleyball games for extracurricular students at SMPN 17 Banda Aceh City. Based on the data analysis conducted, the results of the study showed a significant increase in students' smash accuracy after being given squad jump training. In the descriptive statistical test, the average pretest score was 68.12 with a standard deviation of 5.512, while the average posttest score was 77.62 with a standard deviation of 6.692. This shows a significant increase in the average after the training was carried out. In addition, the results of the normality test using Kolmogorov-Smirnov and Shapiro-Wilk showed that the data were normally distributed, with a p-value greater than 0.05, which means that the normality assumption was met. Hypothesis testing using the Paired Samples Test showed that there was a significant difference between the pretest and posttest scores. The t value = -12.810 with a p-value of 0.000 (p <0.05), which means that the null hypothesis stating that there is no difference between the pretest and posttest can be rejected.